ANALYSIS STRATEGIC ENTREPRENEURSHIP MODEL IN BOGOR CITY CULINARY SMEs - Widya Pertiwi, Intan; Kartika, Lindawati (Indonesian Journal of Business and Entrepreneurship, 2021)
The growth of SMEs in Bogor city creates intense competition and requires businesses to be more strategic by utilizing business opportunities and seeking competitive advantage by adopting a strategic entrepreneurial model. The purpose of this study was to identify the management of strategic entrepreneurship in culinary SMEs in Bogor City and analyze the influence between the elements of input, processes, and output of the strategic entrepreneurship model. This research used descriptive analysis and the SEM-PLS method. The implementation of strategic entrepreneurship in Bogor City culinary SMEs has been in an excellent performance. It is based on the average results of each variable more than 3.4, which is categorized as very good. The results of SEM-PLS analysis showed that the environmental factors, organizations, and individuals influenced the orchestration of resources and strategic entrepreneurship affected the output of creating competitive advantage and creating wealth and benefits for individuals, organizations, and society. Keywords: competitive advantage, culinary, opportunities, strategic entrepreneurship, small medium enterprise (SMEs)